2007
DOI: 10.1055/s-2007-992178
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Facial Movements in the First Minutes of Life-Eye Opening and Tongue Thrust: An Observational Study

Abstract: Infants born by caesarean section (CS) near or at term were observed to display spontaneous facial movements in their first minutes. We hypothesized that those are reproducible. Up to now, nothing was known about the significance, frequency, and determinants of such facial activity. Repetitive eye opening (EO) and tongue thrust (TT) actions were documented during 1 to 5 minutes, 5 to 10 minutes, and 1 to 15 minutes in 102 infants. In addition, 32 infants were recorded on video from minute 2 to minute 10. Infan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 16 publications
(16 reference statements)
0
16
0
Order By: Relevance
“…Day 14 findings are likely related to infant characteristics for those infants remaining in the hospital. Improved behavioral organization immediately prior to feeding has the potential to facilitate complete oral feeding (Erlandsson et al, 2007; Hentschel et al, 2007; Matthiesen et al, 2001; Ransjo-Arvidson et al, 2001; Widstrom et al, 1987). However, there are there are no other feeding readiness interventions that address changes in orally directed behaviors and behavioral state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Day 14 findings are likely related to infant characteristics for those infants remaining in the hospital. Improved behavioral organization immediately prior to feeding has the potential to facilitate complete oral feeding (Erlandsson et al, 2007; Hentschel et al, 2007; Matthiesen et al, 2001; Ransjo-Arvidson et al, 2001; Widstrom et al, 1987). However, there are there are no other feeding readiness interventions that address changes in orally directed behaviors and behavioral state.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated episodes of swiping at mouth are considered a less organized behavior whereas a sustained hand to mouth is more difficult to achieve and is considered a more organized behavior (Bell et al, 2012). In full-term infants, high frequency of orally directed behaviors is associated with successful latch and sustained breastfeeding (Erlandsson, Dsilna, Fagerberg, & Christensson, 2007; Hentschel, Ruff, Juette, von Gontard, & Gortner, 2007; Ransjo-Arvidson et al, 2001). …”
Section: Orally Directed Behaviorsmentioning
confidence: 99%
“…Early human research by Stern (1977), Oliver and Oliver (1978) and others led to the advocation of uninterrupted face-to-face contact between mother and baby following delivery to 'cement' the attachment between them. In later work, German researchers Hentschel et al (2007) hypothesised that it is innate in human newborns to actively try and engage their mother almost immediately following birth.…”
Section: Discussionmentioning
confidence: 99%
“…Sequential spontaneous behaviour of wide eye opening followed by the seeking mouth gaping and the tongue moving downwards and forwards, usually in the first fifteen minutes of life, signals the mother, who has evolved as an active participant in the latching process, of the nearing readiness to feed 20, 21.…”
Section: Early Instinctual Behaviour In Animals and Newborn Infantsmentioning
confidence: 99%
“…It has been observed that newborn babies proceed to open their eyes widely after birth 20 occurring about 5–20 minutes after an initial blinking phase. Following this, the mouth opens and the tongue descends and protrudes.…”
Section: Future Researchmentioning
confidence: 99%